Numerical investigation on the effect of harmonic horizontal-axis rotation on laminar natural convection in an air-filled enclosure. (May 2020) - Yu, Guojun; Lian, Zhiwei; Gan, Wei; Ji, Jun
Highlights: The mathematical model for natural convection in a harmonic rotation enclosure is established in a non-inertial frame, with the non-inertial forces fully considered. The thermal and hydraulic behavior of the natural convection is found to present different features in the three proposed scenarios of the combinations of the dimensionless parameters. The harmonic rotation is found to enhance the heat transfer, and the mechanism of heat transfer enhancement is explained by the interaction of the gravitational buoyancy and additional forces induced by harmonic rotation. Abstract: A numerical study is performed to clarify the effect of a harmonic horizontal-axis rotation on the laminar natural convection in an air-filled enclosure. The mathematical model is established in a non-inertial frame, with the tangential, Coriolis, centrifugal forces as well as their induced-buoyancy forces fully considered. Dimensionless governing equations are developed with Prandtl number, Rayleigh number ( Ra ), together with two newly defined dimensionless parameters for the harmonic-rotation convection problem, namely nominal rotational Rayleigh number ( R a ˜ ω ) and nominal Taylor number ( T a ˜ ). The dimensionless governing equations are discretized using the finite volume method (FVM), and then solved by an inner doubly iterative efficient algorithm for linked equations (IDEAL). Further, a computer code is developed and its results are validated using those obtained via Ansys Fluent software with a dynamic mesh as well as those reported in similar studies in the literature. In particular, the effect of the harmonic rotation on natural convection is investigated for three different parameter combination scenarios, T a ˜ > R a > R a ˜ ω, R a > T a ˜ > R a ˜ ω and T a ˜ > R a ˜ ω > R a, respectively. The results indicate that the flow and heat transfer behavior are determined by the combined effect of gravitational buoyancy force, inertial forces and their induced buoyancy forces, and the different scenarios of dimensionless parameters present different thermal and hydraulic characteristics owing to different force interactions. It is also found that heat transfer is enhanced by the harmonic rotation, and the heat transfer enhancement is the largest and most sensitive to harmonic rotation when T a ˜ > R a ˜ ω > R a, followed by T a ˜ > R a > R a ˜ ω and then R a > T a ˜ > R a ˜ ω . In addition, the mechanism of heat transfer enhancement is also clarified. This study provides a fundamental insight into thermal and hydraulic characteristics of natural convection or even forced convection in harmonic rotation systems.